Propagation of Large Spalls in Rolling Bearings - Guillermo E. Morales-Espejel (Japanese Society of Tribologists, 2019)
The paper focuses on studying the propagation of large spalls on the raceways of rolling bearings. This is done by means of experiments and modelling. It is shown that the application of a relatively simple model to describe a spall evolution in time in rolling bearings is feasible. The proposed model is validated using experiments, where rolling bearings with initial pre-damage have been tested and the surface spall progression has been monitored in time. Surprisingly, spall progression in rolling bearings appears to be correctly described by a model of damage initiation. Without the need of a more sophisticated crack propagation model, at least this seems to be the case for a relatively large spall (larger than the Hertzian contact). Where the effects of the pressure build up from lubrication can be ignored. However, dynamic effects cannot be disregarded, since they seem to be the driving force for the propagation direction in some cases. The effect of the shape, size of the initiation point and load sequence is studied as well as the shape of the contact (line or elliptical), giving interesting insights of the propagation mechanisms.